Efektivitas Undang-Undang Tentang Konservasi Sumber Daya Alam Dan Ekosistemnya Terkait Tindak Pidana Perdagangan Penyu Ilegal Di Ditpolairud Polda Bali - I Kadek Merta Dana; Putu Sekarwangi Saraswati (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
It is illegal to capture, injure, kill, or trade protected animals alive, as stated in Article 21, Paragraph (2) Letter an of Law Number 5 of 1990, which aims to eradicate illegal turtle trade also protect natural resources and their ecosystems. Because this study focuses on field data also current community concerns, it employs empirical legal research technique for analyzing community legal behavior. This research takes a descriptive technique, which is characterized by the use of written language to explain the phenomena in its natural habitat. The study revealed illicit turtle trade crime has not been properly prosecuted due to lack deterrent impact from penalties also imprisonment